2011
DOI: 10.14742/ajet.971
|View full text |Cite
|
Sign up to set email alerts
|

An information-summarising instruction strategy for improving the web-based problem solving abilities of students

Abstract: As knowledge rapidly expands and accumulates, training and assessing students' information searching ability for solving problems on the Internet has become an important and challenging issue. This research aims to improve the web-based problem solving abilities of primary school students by employing an information summarising approach for improving their skills in using keywords and extracting proper information. Moreover, a web-based learning environment is employed to record and analyse the online informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…Tu, Shih, and Tsai (2008) pointed out that students' epistemological beliefs played an important role in students' OISS. Some studies even reported that students' OISS was improved when they completed related online training activities (Hwang & Kuo, 2011;Tekinarslan, 2008).…”
Section: Online Information Searching Strategies (Oiss)mentioning
confidence: 99%
“…Tu, Shih, and Tsai (2008) pointed out that students' epistemological beliefs played an important role in students' OISS. Some studies even reported that students' OISS was improved when they completed related online training activities (Hwang & Kuo, 2011;Tekinarslan, 2008).…”
Section: Online Information Searching Strategies (Oiss)mentioning
confidence: 99%
“…As there is evidence that peer‐to‐peer collaboration produces higher instances of planning and evaluating, and higher learning outcomes (Lazonder, 2005), more research is needed concerning IPS and collaboration (Lazonder & Rouet, ). Whereas the research mainstream in this field has focused on the study of individual skills (Raes et al, ), several recent studies (Badia & Becerril, ; Lee & Cho, ; Shah, ; Wu, Hwang, & Kuo, ) have focused on small groups and some new collaborative aspects have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, A high search outcome student usually plays the role of leader to demonstrate how he/she solves problems by defining the information problem, searching for information, scanning, processing, and organizing the information, during which the middle search outcome and low search outcome members can observer and reflect. Thus, the middle search outcome and low search outcome members are allowed to question the high search outcome peer at any time when conducting problem solving (Lee, Hsieh, & Hwang, 2011;Hwang & Kuo, 2011;Hwang, Chen, Tsai, & Tsai, 2011;Tseng, Hwang, Tsai & Tsai, 2009). The collaboration has an important effect on the learning performance of students.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Moreover, social searching behaviors might enrich student's learning experience by motivating them to seek new insights and perspectives (Hwang & Kuo, 2011). We used the system log and post-test to determine the relationship between their social searching behaviors and learing outcomes.…”
Section: Analysis Of Learning Behaviors and Learning Outcomesmentioning
confidence: 99%